Transkulturowość oryginału w przekładzie (na przykładzie powieści Derviš i smrt Mešy Selimovicia) - Stanios, Iwona (Przekłady Literatur Słowiańskich, 2012)
Transculturality of the original in its translation (based on the Meša Selimović’s novel Derviš i smrt) The article discusses the problem of transculturality that appears in the prototype (that is, the original work), but which partly or completely disappears in its translation. It occurs when a text is translated from a transcultural area (i.e. Bosnia and Herzegovina) into a monocultural area (i.e. Poland). Transculturality of Meša Selimović’s novel Derviš i smrt appears mostly in the language that is characterized by borrowings from Arabic, Persian and Turkish. The borrowings can be divided into 3 categories: words with cultural features, words connected with Islam and words connected with the place (Bosnia and Herzegovina). Since every language comprises the history and culture of the nation, the Serbian language is marked with the 500-year-long Ottoman occupation. It is impossible to find equivalents for those borrowings in the Polish language as there are no words with such emotional and historical features. The translator can use either reduction or amplification in these situations, but it will definitely distort the understanding of the novel as the primary and secondary receivers have different cognitive structures and some words will trigger different idealized cognitive models in their minds. In conclusion, the transculturality makes the novel difficult to translate because of the impossibility to find equivalents and because of the differences in the primary and secondary receivers’ cognitive structures. Key words: Bosnia and Herzegovina, cognitive structures, idealized cognitive models, Meša Selimović, transculturality.